Pemanfaatan Teknologi Informasi dalam Manajemen Perkantoran untuk Efektivitas Administrasi dan Pengelolaan Organisasi Dakwah Berbasis Profesionalisme - Parjono; Nuryati; Fauzan Diaz; Sugianto; Meity Suryandari (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study discusses the use of information technology (IT) in the office management of Islamic missionary organizations to improve administrative effectiveness and management professionalism. The research method used is a literature study with a descriptive-analytical approach, reviewing the 2020–2025 literature related to management information systems, office administration, and digital transformation of Islamic missionary activities. The results show that the implementation of IT in Islamic missionary organizations includes the implementation of Islamic Missionary Management Information Systems (MIS), website development, social media utilization, mobile application use, and administrative automation. The use of IT has been proven to support transparency, accelerate services, and expand the reach of Islamic missionary activities, especially to the digital generation. However, challenges such as limited digital literacy, infrastructure, funding, and organizational cultural resistance remain major obstacles. The strategies offered include increasing human resource capacity through digital training, developing SOPs and internal regulations, strengthening digital ethics, and collaboration between Islamic missionary organizations in sharing IT resources. In conclusion, the digitalization of Islamic missionary office management requires integration between technology, human resources, and regulations so that Islamic missionary institutions can adapt professionally and sustainably in the era of digital transformation.